(3QSGdI EjVGM GdJhMjO def JfHg ef SfI GdZadI hYQa GdMb hCHUQ hEKHGJ GdMLIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdEdg GdMGce GdPi CfcQ hLhOg ddZGUHhf GdeaJQhf GdTGchf GdedMOhf hJhSdJ Edjg Hhdi Mbg s
(3BNQgG (B:s
(3Ef gPG dgh GdbUU GdMb heG ef Edg EdG Gddg fLRJ HefI hdi GdCeQ bhHdJ hUMMJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B73s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds